2008
DOI: 10.4049/jimmunol.180.7.4939
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Attenuates Gastrointestinal Candidiasis in Normal and Immunodeficient RAG-2−/− Mice via Peroxisome Proliferator-Activated Receptor-γ Activation

Abstract: We recently demonstrated that in vitro peroxisome proliferator-activated receptor-γ (PPARγ) activation of mouse peritoneal macrophages by IL-13 or PPARγ ligands promotes uptake and killing of Candida albicans through mannose receptor overexpression. In this study, we demonstrate that i.p. treatment of immunocompetent and immunodeficient (RAG-2−/−) mice with natural and synthetic PPARγ-specific ligands or with IL-13 decreases C. albicans colonization of the gastrointestinal (GI) tract 8 days following oral infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 53 publications
4
33
0
Order By: Relevance
“…Enhancement in host defense by PPAR␥ agonists has also been noted in other infectious agents such as Candida albicans, Klebsiella pneumoniae, and Staphylococcus aureus (25)(26)(27)(28)(51)(52)(53)(54). Overall, these findings point toward a key role of PPAR␥ in the macrophage immune response, where the function of PPAR␥ goes beyond an anti-inflammatory role and extends into modulation of host defense.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Enhancement in host defense by PPAR␥ agonists has also been noted in other infectious agents such as Candida albicans, Klebsiella pneumoniae, and Staphylococcus aureus (25)(26)(27)(28)(51)(52)(53)(54). Overall, these findings point toward a key role of PPAR␥ in the macrophage immune response, where the function of PPAR␥ goes beyond an anti-inflammatory role and extends into modulation of host defense.…”
Section: Discussionmentioning
confidence: 71%
“…By binding to PPAR response elements in target genes, PPARs control the expression of broad networks of genes that regulate diverse and fundamental cellular processes, including metabolism and inflammation (20). In recent years, many studies have described the enhancement of host defenses by PPAR␥ in response to infection by various pathogens (25)(26)(27)(28). We sought to delineate one such mechanism by which PPAR␥ agonists can potentially induce downstream effects, such as the upregulation of PON-2, known for its quorum-quenching properties (15).…”
mentioning
confidence: 99%
“…Consistent with our findings, Katsifa et al (21) showed that human monocytes' phagocytosis is increased through mannose receptors in response to IL-13. Later, a series of studies delineated the mechanisms of IL-13 action in a mouse model: i.e., IL-13 increases Dectin-1 and mannose receptor expression by activating PPAR-g, a critical transcription factor for M2 macrophage differentiation, which, in turn, increases M2 macrophage phagocytic activity (22)(23)(24). It is worth noting that human macrophages tend to differentiate into an M2 type in the presence of C. albicans (25), which suggests that animals possess safeguards at multiple stages of Th2 immunity against Candida infection.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, macrophages from these infected mice display an intermediate activation phenotype (47) that is predominantly M2. Although evidence indicates that alternatively activated macrophages are more susceptible to some intracellular pathogens, including Cryptococcus neoformans (49), IL-13 was found to attenuate gastrointestinal candidiasis in normal and immunodeficient RAG-2 Ϫ/Ϫ mice, and this protection was correlated with recruitment of macrophages overexpressing the mannose receptor to the intestinal mucosa (12).…”
Section: Discussionmentioning
confidence: 99%
“…Oral colonization and infection of mice with C. albicans trigger macrophage recruitment to the mucosa of the oral cavity (9), stomach (10,71), and cecum (12), suggesting that these cells play a role in resistance to mucosal candidiasis (68). Activated macrophages have the capacity to kill C. albicans by their production of the reactive oxygen intermediates (ROIs) O 2 Ϫ and H 2 O 2 , by the formation of peroxynitrite from O 2 Ϫ and the reactive nitrogen intermediate NO, and by oxygen-independent candidacidal mechanisms (68)(69)(70)(71)73).…”
mentioning
confidence: 99%